Job Satisfaction and Teaching Performance of Basic Education Teachers in Catholic Schools - Josefina T. Ballarta; Johnny T. Roberto (Philippine Social Science Journal, 2020)
Job satisfaction plays a vital role in the overall commitment and productivity of the school organization. It is more about individual attitude, an internal state which can mean different things to different people.  Job satisfaction can be a positive emotional state resulting from a personal appreciation of a person's work experience.  Recently job satisfaction has been cited as a possible cause of the current educational crisis among private catholic schools in Antique, which results in teacher turnover and absenteeism issues that lead to poor quality education. Hence, the paper describes the level of job satisfaction and the teaching performance of basic education teachers in Antique Diocesan Catholic Schools (ADCS) for the School Year 2019-2020. Likewise, it explores the relationship between teachers’ job satisfaction and their teaching performance.